Permanent Magnetic Synchronous Motor Control System Based on ADRC - Song Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Permanent magnetic synchronous motor (PMSM) is a strong coupling and non-linear system. In the PMSM speed-regulation system, PID controller is the conventional one, it is difficult to decide the parameters of PID. Moreover, the performance of PID controller is not very well in large disturbance. In the paper, the Active Disturbance Rejection Controller (ADRC) is applied to the PMSM speed-regulation system. The result of simulations and experiments show that this algorithm has better anti-load-disturbance performance than PID controller. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2720